Análise temporal de precipitação com teste de Mann-Kendall entre os anos 1981 a 2020 em Corumbá MS - Espíndola, Duani Aparecida Lima Ferbônio (2024)
This study looked into the rainfall trends in the Corumbá area of MS, using the Mann-Kendall test along with CHIRPS satellite data from 1981 to 2020. Corumbá, which is situated in the Pantanal, is noteworthy because of its tropical climate and the socioeconomic effects that come with it. The analysis demonstrated that CHIRPS precipitation data align well with the data from local weather stations. The overall trend observed was an increase in annual rainfall over the years, although there were significant fluctuations between different years. A closer look from 2010 to 2020 revealed that rainfall during the rainy months was decreasing, with this trend proving statistically significant in some months. These findings are crucial for planning water resources and adapting to climate change in the region.